Pengaruh Motivasi dan Beban Kerja Terhadap Produktivitas Kerja Perawat Unit Rawat Inap RSUD Sultan Suriansyah Banjarmasin: Penelitian - Dewi Safitri; Khuzaini; Dwi Wahyu Artiningsih; Zakky Zamrudi; Ana Sofia Herawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Nurse productivity is a crucial factor in improving the quality of hospital services, particularly in inpatient units with high service intensity. Motivation and workload are two key aspects believed to influence nurse productivity. Motivation reflects internal and external drives that encourage nurses to work optimally, while workload relates to the physical, mental, and administrative demands they must fulfill during their duties. This study aims to analyze the effect of motivation and workload, both partially and simultaneously, on the work productivity of nurses at RSUD Sultan Suriansyah Banjarmasin. A quantitative approach was employed using a survey method through questionnaires distributed to inpatient nurses. Data were analyzed using multiple linear regression, including validity and reliability tests, classical assumption tests, and hypothesis testing (t-test and F-test). The results show that motivation has a positive and significant effect on nurse productivity, while workload also has a significant influence but tends to reduce productivity when it exceeds the nurses’ capacity. Simultaneously, motivation and workload significantly affect the productivity of inpatient nurses. These findings indicate that improving nurse productivity requires strengthening motivation, providing a supportive work environment, and ensuring a proportional distribution of workload.